Penguatan Sistem Manajemen Keuangan Melalui Peningkatan Kemampuan Perhitungan Harga Pokok Produksi - Dirman, Angela; Sarpingah, Siti; Utami, Siska Widia (FKIP Universitas Wisnuwardhana, 2025)
In the business world, competition between companies is natural. Each company strives to offer its own unique product offerings. In addition to competing on quality, they also compete on price, as only the highest-quality and lowest-priced products are most sought after and sought after by consumers. Education level, business training, and previous managerial experience can also influence the accounting information reflected in accounting records. Therefore, a lack of education or business management training can make it difficult for entrepreneurs to advance their businesses due to a lack of accurate financial information, leading to ineffective and uncontrolled decision-making. Considering the fact that many small and medium-sized enterprises (SMEs) in the surrounding area are incapable of managing their finances, we were motivated to provide training on calculating COGS and determining selling prices, which can serve as additional knowledge for MSME entrepreneurs. Our community service activities demonstrate Mercubuana University's commitment to the surrounding environment. This is a manifestation of Mercubuana University's efforts to benefit the surrounding community, known as Corporate Social Responsibility (CSR). This community service activity has successfully provided counseling, training, and practical training on calculating the cost of goods manufactured to target partners. The knowledge transfer, covering technological aspects, calculation processes, and preparing simple financial reports, was effective and understood by the participants. Overall, this activity went smoothly and is expected to contribute to improving the economy of the residents of North Kembangan Village.